The Islamic economic policy: some historical accounts on economic policies in the moslem world - Karim, Muhammad Abdul (Universitas Ahmad Dahlan, 2023)
Throughout history, Islamic civilization has witnessed several important events in economic progress. One of the problems faced by Islamic leaders in fostering the people was related to improving people's welfare. In the classical period, some Muslim figures became pioneers in economic policies. In a specific way, the paper tries to analyze economic policies promoted by prominent Muslim figures such as 'Umar bin Khattab, Umar bin' Abdul Aziz, Ghazan Khan, and Alauddin Khalji. By using descriptive analysis, this brief article discusses the economic policies applied by some of the mentioned figures through historical analysis. The data were gathered from books and journals. Throughout critical historical analysis, the paper concluded that some Muslim figures succeeded in bringing Muslims into economic advancement along with some of the policies they came up with.